Self-perceived anxiety symptoms and its associated factors among type 2 diabetic patients in rural communities of Malaysia / Azlina Wati Nikmat, Mohd Ariff Fadzil and Sakinah Idris - Nikmat, Azlina Wati; Mohd Ariff Fadzil; Idris, Sakinah (Faculty of Medicine, 2016)
Little is known about anxiety symptoms among diabetic patients, especially among those who are living in rural areas in Malaysia. Thus, the aim of this paper is to investigate the prevalence of anxiety among diabetic patients and factors associated with anxiety in rural communities in Malaysia. Methods: A cross-sectional study involving 464 diabetes mellitus patients in rural health districts and outpatient clinics in Malaysia was conducted. Each participant was interviewed using the Hospital Anxiety and Depression Scale. Results: Respondents consisted of 193 (41.6%) males and 271 (58.4%) females. The mean age of participants was 59.65 ± 10.16 years and the mean duration of diabetes mellitus was 6.9 ± 6.3 years. Results indicate that 15% of the participants have anxiety symptoms. Multiple logistic regression analysis revealed that patients with history of ischemic heart disease and depression and those who were underweight have higher anxiety scores with adjusted OR 5.06 (95% CI 1.79 to 14.27), 27.71 (95% CI 14.23 to 53.98) and 14.6 (95% CI 2.49 to 84.82), respectively. Conclusions: This study suggests that although the prevalence of anxiety among diabetics is low, primary care physician should be trained to identify high risk patients and to manage their condition in order to improve the clinical outcome.